Experimental investigation of a spark ignition engine fueled with acetone-butanol-ethanol and gasoline blends. (15th February 2017) - Li, Yuqiang; Meng, Lei; Nithyanandan, Karthik; Lee, Timothy H.; Lin, Yilu; Lee, Chia-fon F.; Liao, Shengming
Abstract: Bio-butanol is typically produced by acetone-butanol-ethanol (ABE) fermentation, however, the recovery of bio-butanol from the ABE mixture involves high costs and energy consumption. Hence it is of interest to study the intermediate fermentation product, i.e. ABE, as a potentially alternative fuel. In this study, an experimental investigation of the performance, combustion and emission characteristics of a port fuel-injection SI engine fueled with ABE-gasoline blends was carried out. By testing different ABE-gasoline blends with varying ABE content (0 vol%, 10 vol%, 30 vol% and 60 vol% referred to as G100, ABE10, ABE30 and ABE60), ABE formulation (A:B:E of 1:8:1, 3:6:1 and 5:4:1 referred to as ABE(181), ABE(361) and ABE(541)), and water content (0.5 vol% and 1 vol% water referred to as W0.5 and W1), it was found that ABE(361)30 performed well in terms of engine performance and emissions, including brake thermal efficiency (BTE), brake specific fuel consumption (BSFC), carbon monoxide (CO), unburned hydrocarbons (UHC) and nitrogen oxides (NOx ) emissions. Then, ABE(361)30 was compared with conventional fuels, including E30, B30 (30 vol% ethanol or butanol blended with gasoline) and pure gasoline (G100) under various equivalence ratios and engine loads. Overall, a higher BTE (0.2–1.4%) and lower CO (1.4–4.4%), UHC (0.3–9.9%) and NOx (4.2–14.6%) emissions were observed for ABE(361)30 compared to those of G100 in some cases. Therefore, ABE could be a good alternative fuel to gasoline due to the environmentally benign manufacturing process (from non-edible biomass feedstock and without a recovery process), and the potential to improve energy efficiency and reduce pollutant emissions. Highlights: ABE (acetone-butanol-ethanol) was used as a green alternative fuel. ABE-gasoline blends with various ratios of ABE, ABE component and water were test. Combustion, performance and emissions characteristics were investigated. Adding ABE into gasoline can enhance BTE and reduce CO, UHC and NOx emissions.